Avaliação técnica e econômica do forwarder na extração de madeira em povoamento de eucalipto de primeiro corte - Simões, Danilo [UNESP]; Fenner, Paulo Torres [UNESP] (Universidade Federal do Paraná, 2010)
This study aimed to technically and economically evaluate the Forwarder performance in the first cutting wood extraction from a Eucalyptus grandis plantation. Technical analysis included a movement and timing study by continuous method, and the productivity was determined using the extracted wood volume in cubic meters. Economical analysis included operational costs parameters and wood extraction cost. Results referred to the effective operational performance. Loading and unloading activities responded for more than ¾ of the total time of effective Forwarder operational cycle. Operational costs were influenced by maintenance and repair costs. The estimated cost of extraction was US$ 0.97 per cubic meter.

O objetivo deste trabalho foi avaliar técnica e economicamente o Forwarder em operação de extração de madeira curta em povoamento de primeiro corte de Eucalyptus grandis. A análise técnica englobou um estudo de tempos e movimentos pelo método contínuo e a produtividade foi determinada através do volume em metros cúbicos de madeira extraída. A análise econômica englobou os parâmetros do custo operacional e custo de extração da madeira. Os resultados referem-se ao rendimento operacional efetivo. As atividades parciais carregamento e descarregamento, juntas, corresponderam a mais de ¾ do tempo total do ciclo operacional efetivo do Forwarder. O custo operacional foi seguramente influenciado pelos custos de reparo e manutenção. O custo estimado de extração foi de US$ 0.97 por metro cúbico.
Operational and economical evaluation of the Forwarder in wood extraction from first cutting eucalyptus
Keywords: Production costs; Auto loading; Operational performance; Custos de produção; Auto-carregáveis; Rendimentos operacionais